2023
DOI: 10.1002/adfm.202214657
|View full text |Cite
|
Sign up to set email alerts
|

ZnP‐Coated Zn1Cu0.1Ti Membrane with High Strength‐Ductility, Antibacterial Ability, Cytocompatibility, and Osteogenesis for Biodegradable Guided Bone Regeneration Applications

Abstract: Zinc (Zn) and its alloys have recently gained research interest due to their good biosafety, biological function, biodegradability, and formability. Zincphosphate (ZnP) coating has been shown to improve the corrosion resistance and biocompatibility of Zn alloys. Here, a biodegradable ZnP-coating on Zn1Cu0.1Ti (ZCT) membrane with high strength-ductility and mechanical stability, suitable degradation rate, effective antibacterial ability, excellent in vitro and in vivo cytocompatibility, and osteogenesis is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…Besides, previous studies have also confirmed that the osteogenic and antibacterial activity of pure Zn implants are grossly inadequate. , Until now, Zn-based alloys are still facing some challenges to serve as a platform in GBR because the antibacterial effects of Zn 2+ have been mostly explained by dosage-dependent cytotoxicity . It implies that the therapeutic window for Zn 2+ favoring osteogenesis could exhibit limited antibacterial effects, which was also confirmed in other research works. ,, Even though the degradation of Zn-based materials and Zn 2+ leaching kinetics can be precisely controlled, it is still difficult to balance their antibacterial, osteogenic, and angiogenic effects only relying on single Zn 2+ for GBR application.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Besides, previous studies have also confirmed that the osteogenic and antibacterial activity of pure Zn implants are grossly inadequate. , Until now, Zn-based alloys are still facing some challenges to serve as a platform in GBR because the antibacterial effects of Zn 2+ have been mostly explained by dosage-dependent cytotoxicity . It implies that the therapeutic window for Zn 2+ favoring osteogenesis could exhibit limited antibacterial effects, which was also confirmed in other research works. ,, Even though the degradation of Zn-based materials and Zn 2+ leaching kinetics can be precisely controlled, it is still difficult to balance their antibacterial, osteogenic, and angiogenic effects only relying on single Zn 2+ for GBR application.…”
Section: Introductionmentioning
confidence: 59%
“…14 It implies that the therapeutic window for Zn 2+ favoring osteogenesis could exhibit limited antibacterial effects, which was also confirmed in other research works. 9,12,15 Even though the degradation of Zn-based materials and Zn 2+ leaching kinetics can be precisely controlled, it is still difficult to balance their antibacterial, osteogenic, and angiogenic effects only relying on single Zn 2+ for GBR application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the surface microstructures designed to mimic extracellular matrix (ECM) have caught the attention of researchers. 24–26 In recent years, some organic 27,28 /inorganic 29,30 and composite coatings 25,31,32 have been reported to improve the osseointegration ability of Zn-based orthopedic implants. Thereinto, zinc phosphate (ZnP) and hydroxyapatite (HA) coatings have gained popularity due to their demonstrated effectiveness in reducing corrosion rates, suppressing Zn 2+ release, and enhancing osteogenic activity of Zn-alloy substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from osseointegration with host bone tissues and vascular connection, GBR membranes are expected to inhibit bacterial activity in an open oral environment since bacteria breeding can both reduce bone augment and new attachment around teeth. 12 Metallic Mg has been proven to be bacteriostatic when the concentration of Mg 2+ ions and pH of the degradation medium are over 300 ppm and 9.5 simultaneously. 13 However, such an environment in body fluids has been demonstrated to be chronically toxic to cells and beyond the acceptable threshold value for the human body.…”
Section: Introductionmentioning
confidence: 99%